The New Procedures of the Central Bank of Iraq after 2003 - Fadel Krayah Kazaar Al-Shaibani (Journal of Madenat Alelem University College, 2021)
After 2003, the Iraqi economy witnessed a new phase, in which the most important changes took place. The Central Bank of Iraq gained independence, in accordance with Law No. (56) for the year 2004, in determining the monetary policy, and determining appropriate tools in implementing this policy, and the identification of appropriate tools in the implementation of that policy, as well as the development of new tools to suit the orientations of the objectives of the Central Bank in Iraq. The most important of which is the stability of prices and raise the value of the Iraqi dinar through two price signals exchange rate and interest rate, as these new tools are characterized as enabling the central bank to control the volume of credit at the macro level indirectly and more subject to the rules of supply and demand in the market.      The research is divided into four sections. The first one is the technical and organizational means and procedures developed by the Central Bank of Iraq, in addition to the legislative and legal procedures. The second section included the new monetary means, while the third section is the use of the two interest rate and exchange rate to raise the value of the Iraqi dinar, and finally conclusions and recommendations, that included the use of indirect monetary instruments used by the Central Bank of Iraq after 2003 was a safety valve in addressing the problem of inflation through the withdrawal of excess liquidity and the adoption of the exchange rate signal to counter inflation pressures ,and achievement of stability has played a clear role in stabilizing prices, low inflation rates and improving the value of the Iraqi dinar, through foreign currency auctions.